Trasporti, ICT e la città. Perché alla città interessano le ICT? - Delponte, Ilaria (TeMA - Journal of Land Use, Mobility and Environment, 2012)
The paper is focused on the existent relationship among the three elements cited in the title. The innovation in transportation, allowed by new ICT solutions is one of the most important point of development for cities nowadays: this, not only for the process of rationalization and reduction of externalities due to urban mobility, but also and above all thanks to the economic dynamics that technological knowledge boosts in those cities in which local entities, enterprises and research gather together and grow in terms of competitiveness. Deepening transportation, new solutions have main outcomes in the field of the road safety, street security, urban traffic, harbor handling, territorial risks (environmental and industrial), to cite a few. All of these topics own many connections with the work of planners.According to what technology allowed to them, they are expected to exploit it keeping advantage by the new discoveries in current planning activities, in dialogue of the new ITS. The paper ends up that technology involvement in transport is carrying on a new way of planning them and tries to draw out some further conclusions regarding the intervention on existent cities in a changing world and the demand of updated skills in the planning field. To better clarify future findings, the author propose a case-study, referring to the projects of the Innovation Pole of Advanced Research in Safety, Security and Intermodality in Transport Systems, sited in Genoa (IT), inserted in a step-wise logic of development of regional competitiveness and clusterization.